Cyclosporine A-induced nephrotoxicity is ameliorated by dose reduction and conversion to Sirolimus in the rat - Sereno, J. (2015)
Side-effect minimization strategies to avoid serious side-effects of cyclosporine A (CsA), such as nephrotoxicity, have been mainly based on dose reduction and conversion to other putatively less nephrotoxic drugs, such as sirolimus (SRL), an inhibitor of the mammalian target of rapamycin. This study intended to evaluate the impact of protocols based on CsA dose reduction and further conversion to SRL on kidney function and lesions, based on serum, urine and renal tissue markers. The following 3 groups (n=6) were tested during a 9-week protocol: control (vehicle); CsA (5 mg/kg/day) and Red + Conv (CsA 30 mg/kg/day during 3 weeks + 3 weeks with CsA 5 mg/kg/day + SRL 1 mg/kg/day during the last 3 weeks). The following parameters were analysed: blood pressure, heart rate and biochemical data; serum and urine contents and clearances of creatinine, urea and neutrophil gelatinase-associated lipocalin, as well as, glomerular filtration rate; kidney lipid peroxidation and clearance; kidney lesions were evaluated and protein expression was performed by immunohistochemistry. After the first 3 weeks of CsA (30 mg/kg/day) treatment animals showed body weight loss, hypertension, tachycardia, as well as, increased serum levels of non-HDL cholesterol, glucose, triglycerides, creatinine and urea, accompanied by decreased GFR and insulin levels. In addition, a significant increase in the expression of connective tissue growth factor, Kim-1, mammalian target of rapamycin, nuclear factor-κβ1 and transforming growth factor-β was found in the kidney, accompanied by extensive renal damage. The following 3 weeks with CsA dose reduction revealed amelioration of vascular and glomerular lesions, but without significant tubular improvement. The last 3 weeks with the conversion to sirolimus revealed high serum and urine NGAL contents but the CsA-evoked renal damage was substantially ameliorated, by reduced of connective tissue growth factor, mammalian target of rapamycin, nuclear factor-κβ1 protein expression. In conclusion, CsA nephrotoxicity is dose dependent and moderate dysfunction could be ameliorated/prevented by SRL conversion, which could be pivotal for the preservation of kidney function and structure.